Analysis of Accounting Information Systems on the Effectiveness of Transaction Processes and Reporting at PT. PNM Unit Mekaar - Yayat Solihah; A Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted to determine the effectiveness of the transaction process and reporting using the accounting information system at PT. PNM Mekaar. Before the accounting information system was implemented, the transaction process and daily transaction reporting at the Mekaar office were still manual. This research was conducted to find out how the use of accounting information systems on the effectiveness of transaction processes and reporting at PT. PNM Mekaar. The research method used is the research method by direct practice and interviews with reference to the Technology Acceptance Model (TAM) theory. From the results of research conducted on the use of Accounting Management Information Systems on the Effectiveness of Transaction Processes and Reporting at PT. PNM Mekaar, there are 5 integrated applications consisting of Mekaar Initiation, Mekaar Initiation Back Office, PKM Mobile, PKM Mobile Back Office and Mekaar Integration. The accounting information system that is used is useful and easy to use by users, as the user's willingness is higher which results in increased levels of use, causing system error/down constraints